Possibilities of Corn Seed Commercialization on the Hungarian Market in 2003 - Sedlák, Gergő (Acta Agraria Debreceniensis, 2004)
According to the sales results of the past two years we can draw the conclusion that although the Hungarian hybrids have very good capabilities, they are still in a big disadvantage in the corn seed sales sector, considering other foreign varieties. These above mentioned disadvantages, as published in prior essays, are not because of the variety’s low quality, but the lack or little presence of marketing. In order to gain position and market on the seed sales sector in Hungary, a lot more has to be done in the area of advertisement.Seed advertising is very particular and different from all other types of goods. To make growers familiar with your product, you have to be in continuous contact with them, through field days, exhibitions and presentations, besides the well known and in other areas also used quotidian advertisement methods.Although Hungarian breeders reach better and better results each year, they still cannot catch up with the multinational companies spending millions of dollars on development and advertising, thanks to their financial position.Finally we can state that choosing the appropriate variety for our needs and possibilities of land and machinery is of great importance in order to reach the best results we can.